CONCEPTUAL BASIS OF MANAGEMENT OF ECONOMIC SECURITY OF ENTERPRISES - BAIDALA, Viktoriia; YAKYMOVSKA, Anna (Herald of Khmelnytskyi National University. Economic sciences, 2023)
The article is devoted to the study of the conceptual foundations of economic security management of enterprises. The concepts of "security", "economic security" and "management of economic security of enterprises" are considered. It was determined that the economic security of the enterprise is the state of its protection against the negative influence of external and internal threats, destabilizing factors.In general, the management of economic security can be considered as the process of developing and implementing a set of measures aimed at countering threats to the external and internal environment of the enterprise.Objects, subjects, goals, tasks and elements of economic security are considered. The main goal of managing the economic security of the enterprise is determined - this is to ensure its stable and maximally effective functioning now and to increase and ensure the level of enterprise security in the future. The functional goals of economic security are indicated. It is emphasized that the implementation of each of these goals of economic security of the enterprise must support the sustainable functioning of the enterprise. Detailed development and control over the implementation of the target structure of economic security of the enterprise is an important aspect of the process of provision.External and internal threats are singled out. Quantitative and qualitative analysis of the threats presented in the study allows us to conclude that reliable protection of the economy of any enterprise is possible only with a comprehensive and systematic approach to its organization.The conceptual foundations of the management of economic security of enterprises are analyzed and determine the general aspects and principles that guide the strategy and activities of the enterprise to ensure stability and protection against economic threats and risks. It was determined that the given conceptual foundations form the foundation for the development of specific strategies and actions for managing the economic security of the enterprise, contribute to ensuring the stability and sustainability of the enterprise’s activities in conditions of danger and adverse factors.
Keywords: management; enterprise; economic security; management of economic security of enterprise; threats